Thermal Characteristics Testing and Analysis of Dry Gear Hobbing Machine on Multivariate Information Fusion - Peng Shengdi; Yang Xiao; Li Benjie; He Lang; Zhang Zhili (Jixie chuandong, 2024)
Aiming at the problem of thermal characteristics of dry-cutting hobbing machine, research on multi-source information fusion test and analysis is carried out. Based on the analysis of the structure layout and the law of multi-source heat generation and heat dissipation of the dry gear hobbing machine, the testing scheme of its thermal characteristics is established. Through the selection of hardware for the lower computer, the development of software functions for the upper computer, and the integration of test functions, the multi-source fusion test method for the thermal characteristics of dry-cutting and hobbing machine was constructed. Based on the IPO model, it put forward the sequential processing method of multi-source thermal data of dry-cutting and hobbing machine. using outlier replacement, moving average filtering, wavelet filtering, and data resampling, it realised the accurate analysis of multi-source thermal data. The dry roll-cutting machining experiment of an automotive gear is used for verification and analysis, and the results show that the proposed testing and analysis method has high validity and reliability. Through this study, the on-line measurement and accurate analysis of the thermal characteristics of the dry hobbing machine are realised, which can provide support for the thermal balance design of the dry hobbing machine.